Percutaneous stenting as treatment for chylothorax from superior vena cava syndrome: A case report - Arta Kasaeian; Taylor Hoffman; Mohammad Ghasemi Rad; David Wynne; David Léon (SAGE Open Medical Case Reports)
Superior vena cava syndrome is a condition that results from obstruction of the superior vena cava, the etiology of which can be benign or malignant. The impaired venous return can cause facial and upper extremity swelling, dyspnea, and neurologic symptoms. Chylothorax is a rare complication of superior vena cava syndrome. We report a case of a 69-year-old male with end-stage renal disease, who developed both a chylothorax and a contralateral simple pleural effusion secondary to superior vena cava syndrome. He was successfully treated with percutaneous endovascular stenting.